Interspecies Gene Transfer as a Method for Understanding the Genetic Basis for Evolutionary Change: Progress, Pitfalls, and Prospects - Nikolov, Lachezar A.; Tsiantis, Miltos (Frontiers in Plant Science, 2015)
The recent revolution in high throughput sequencing and associated applications provides excellent opportunities to catalogue variation in DNA sequences and gene expression between species. However, understanding the astonishing diversity of the Tree of Life requires understanding the phenotypic consequences of such variation and identification of those rare genetic changes that are causal to diversity. One way to study the genetic basis for trait diversity is to apply a transgenic approach and introduce genes of interest from a donor into a recipient species. Such interspecies gene transfer (IGT) is based on the premise that if a gene is causal to the morphological divergence of the two species, the transfer will endow the recipient with properties of the donor. Extensions of this approach further allow identifying novel loci for the diversification of form and investigating cis- and trans-contributions to morphological evolution. Here we review recent examples from both plant and animal systems that have employed IGT to provide insight into the genetic basis of evolutionary change. We outline the practice of IGT, its methodological strengths and weaknesses, and consider guidelines for its application, emphasizing the importance of phylogenetic distance, character polarity, and life history. We also discuss future perspectives for exploiting IGT in the context of expanding genomic resources in emerging experimental systems and advances in genome editing.